Efficacy of a Group Psychoeducation Treatment in Binge Eating Disorder: An Open-Label Study - Liquori, Silvia; Faidutti, Giovanni; Garzitto, Marco; Saetti, Luana; Bendotti, Monica; Balestrieri, Matteo (Frontiers in Psychiatry, 2022)
Aims To evaluate the effectiveness of a multidisciplinary group psychoeducation treatment (GPT) in patients with Binge Eating Disorder (BED). Methods We designed an open-label efficacy study that included a population of 45 patients diagnosed with BED. A measure of eating attitudes and associated psychological constructs was obtained through the use of the self-report instruments Eating Disorder Inventory (EDI-3), Binge Eating Scale (BES) and Body Uneasiness Test (BUT). The Symptom Checklist-90 (SCL-90) was also administered to assess general psychopathology. All participants participated in 12 weekly group psychoeducational treatment meetings, 8 of which were conducted by mental health professionals, and a second module of 4 meetings, oriented on health and nutrition education topics, conducted by a dietician. Results At the end of treatment, patients showed significant improvements in body mass index (BMI) and binge eating. Paired t-tests showed significant differences at p-value < 0.05 in all eating disorder risk scales and for most of the general psychological scales related to eating disorders. In addition, patients experienced an improvement in their perception of overall body image, a decrease in concerns about physical appearance and less body image avoidance. Finally, results showed that psychoeducation treatment was associated with significant improvements in interpersonal sensitivity. Conclusions The results of this study may indicate that significant short-term improvements can be achieved through a psychoeducation group for BED patients. Although limited by the lack of a control condition, this study adds to a growing body of evidence with promising results, setting the stage for further case-control studies of BED treatment.